2011
DOI: 10.1261/rna.2658311
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogenes: Pseudo-functional or key regulators in health and disease?

Abstract: Pseudogenes have long been labeled as ''junk'' DNA, failed copies of genes that arise during the evolution of genomes. However, recent results are challenging this moniker; indeed, some pseudogenes appear to harbor the potential to regulate their protein-coding cousins. Far from being silent relics, many pseudogenes are transcribed into RNA, some exhibiting a tissuespecific pattern of activation. Pseudogene transcripts can be processed into short interfering RNAs that regulate coding genes through the RNAi pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
324
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(332 citation statements)
references
References 82 publications
2
324
2
4
Order By: Relevance
“…These are the "relics" of genes that have lost their coding potential due to nonsense, frameshift, and other mutations (Balakirev and Ayala 2003;Pink et al 2011). Many pseudogenes are products of tandem gene duplication or of mRNAs being carried along during retrotransposition, both of which create extra gene copies that are no longer under selective pressure.…”
Section: Pseudogenesmentioning
confidence: 99%
“…These are the "relics" of genes that have lost their coding potential due to nonsense, frameshift, and other mutations (Balakirev and Ayala 2003;Pink et al 2011). Many pseudogenes are products of tandem gene duplication or of mRNAs being carried along during retrotransposition, both of which create extra gene copies that are no longer under selective pressure.…”
Section: Pseudogenesmentioning
confidence: 99%
“…Recent studies have shown that processed pseudogenes function in gene regulation. 27) Therefore, we focused on the relationship of pcRNAs and pseudogenes, as described later. Figure 3 shows Venn diagrams of all RNAs, pcRNAs and pseudogenes classified by Emsembl annotation.…”
Section: Sequencing and Annotation Of Rnas From Salivary Exosomes Andmentioning
confidence: 99%
“…Interestingly, transcribed pseudogenes, including those that arose via retroposition, reportedly can be functional as RNAs or mRNAs encoding truncated proteins (Balakirev and Ayala 2003;Duret et al 2006;Frith et al 2006b;Pink et al 2011;Wen et al 2012;Sen and Ghosh 2013). For example, retropseudogene PTENP1 derived from tumor suppressor gene PTEN is transcribed.…”
Section: Competitive Rnasmentioning
confidence: 99%